Characteristics of double-peaked particle deposition at divertor target plates in the EAST tokamak. (21st July 2021) - Xu, J.C.; Wang, L.; Wang, H.Q.; Xu, G.S.; Liu, J.B.; Li, A.; Meng, L.Y.; Wu, X.Q.; Yu, L.; Ding, F.; Jia, G.Z.; Guo, H.Y.; et al.
Abstract: Increasing the heat and particle deposition on the divertor target plates is an effective approach for reducing the extremely high heat load. Future tokamak fusion devices are expected to have a deposition width on the order of a millimeter. Recently, a double-peaked distribution (DPD) pattern of particle deposition at the divertor target plates has been observed in both deuterium and helium plasma discharges in the Experimental Advanced Superconducting Tokamak, which can significantly spread the deposition width of heat and particle fluxes, and clearly shows a toroidal symmetric distribution. It has been found that the DPD behavior occurs not only in plasma discharges with lower hybrid wave (LHW) heating, but also with electron cyclotron resonance heating or neutral beam injection (NBI) heating alone. In addition, the DPD shows an obvious in–out asymmetry between the divertor target plates, which strongly depends on the toroidal field direction, i.e. it distinctly appears on the outer divertor plate in unfavorable B t conditions, while shifting to the inner divertor plate under favorable B t conditions. Meanwhile, the transition between the single-peaked distribution and the DPD is normally correlated with the line-averaged plasma density n ̄ e and the auxiliary heating power. The statistical results for the pure LHW heating discharge scheme show that the DPD behavior is significantly affected by both the plasma density and the heating power, i.e. the lower the ratio of the plasma density to the heating power, the more likely it is that DPD behavior will occur. The critical boundary lines between the DPD and non-DPD patterns are obtained with the line expressions n ̄ e ∼ 2 P LHW, abs + 1.4 and n ̄ e ∼ 3.33 P LHW, abs + 1 for the unfavorable and favorable B t cases, respectively. Finally, the underlying physics is also discussed, suggesting that the electric field drifts and the local sheath boundary condition may exert a strong influence on the DPD.